Experimental study of Λ(1405) via the d(K- ,πΣ) reaction at J-PARC K1.8BR - Omar, Zh. (Хабаршы. Физика сериясы, 2019)
The Λ(1405) baryon resonance plays an outstanding role in various aspects of hadron and nuclear physics. It has been considered that the Λ(1405) resonance is generated by the attractive interaction of the antikaon and the nucleon as a quasi-bound state below its threshold decaying into the πΣ channel. Thus, the structure of Λ(1405) is closely related to KbarN interaction. In this paper, after reviewing the basic properties of the Λ(1405) resonance and introduction to the experiment, which is performed at the K1.8BR beamline in the Hadron Experimental Hall of J-PARC, Tokai, Japan in January and February 2018, we introduce the spectral shapes which are taken by the data analysis. We have finished a beam time and data taking for the second run of E31. In the second run, we could increase the statistics several times. Based on the second run data, we analyzed the Σ+π- and Σ-π+ invariant mass spectra in the d(K-, Σ+π-)"n" and d(K-, Σ-π+)"n" reactions, respectively, where "n" is clearly identified in the missing mass spectrum of each reaction. Also, we considered the background events to estimate the sideband and get the correct peak structure of Λ(1405).We summarize the recent progress in the investigation of the Λ(1405) structure and discuss the future perspective of the physics of the Λ(1405) resonance.